Studi Komparatif Kinerja Bank Syariah Dan Bank Konvensional Dalam Menghadapi Krisis Global Berdasarkan Rasio Keuangan - Rohmawati Kusumaningtias (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2009)
AbstractAt the time of financial crisis, one of the influential institutions in society is banking. Banking sector provide soft loans to create productive employment for the community. On the other hand, customers also need the liquidity from bank-ing. These stakeholders' needs can be met by looking at the performance of bank-ing. This study aims to determine differences in the performance of sharia banking and conventional banking during economic crisis. This study uses t-test to analyze the data. From the research, it was found that in general, the performance of conventional banking is better than sharia banking in the economic crisis.